A proximity‐based image‐processing algorithm for colloid assignment in segmented multiphase flow datasets - BRUECK, C.L.; WILDENSCHILD, D. (Journal of microscopy (Oxford), 2020)
Summary Colloidal transport and deposition are of both environmental and engineering importance. Easier access to x‐ray microtomography (XMT) coupled with improved imaging resolution has made XMT a unique and viable tool for visualizing and quantifying these processes. Currently, there is scant information in the literature addressing colloid segmentation and analysis in saturated and unsaturated porous media, in particular related to spatial partitioning of colloids. To support this need, an approach to assign segmented colloidal particles and aggregates to different partitioning classes based on their proximity to different phases is presented here. The method uses different markers for each attachment site (e.g. wetting‐nonwetting phase interfaces). An example XMT dataset from a drainage experiment is used to demonstrate the efficacy of the image processing algorithms. Flow conditions, and fluid and colloid properties, can thus be compared to the behaviour of colloids within the porous medium. This algorithm can help elucidate colloidal deposition mechanisms and the importance of different attachment sites, explore the importance of fluid properties, as well as the arrangement and shape of the colloids. Lay Summary Chemical or biological contaminants (pollutants, bacteria etc.) may attach to soil particles, or colloids, and move throughout the environment. This leads to contamination of surface water and groundwater. Our approach to study the fate of these colloids is to use an imaging technique called x‐ray microtomography (XMT), which allows us to look inside otherwise opaque materials. Thus, we can directly observe how particles move when in the presence of multiple phases (e.g. water, air, soil) with varying chemical properties and surface characteristics. After the microtomography 3D scans are collected, a challenge that remains is how to process the data to glean meaningful quantitative results. This research provides an approach for how to design an XMT study to answer colloid transport‐related questions, how to process the raw data into a quantifiable format, and lastly provides an algorithm that groups colloids together based on where they are located in the porous medium. With this toolset, scientists can investigate the innerworkings of a flow experiment and directly observe and quantify attachment and detachment of colloids under varied experimental conditions. These analyses will complement traditional column transport studies, providing a deeper understanding of the fundamental transport behaviour, and ultimately providing insight in how best to protect our water resources.